Guidance on tasks and deliverables for different evaluation phases (Methods Lab, 2015)
This tool describes the five key phases of evaluation, from planning and design, to implementation and communication of results. It provides a list of the main tasks and deliverables for each phase, intended for use by anyone managing an impact evaluation. This tool was developed by Irene Guijt, Simon Hearn, Tiina Pasanen and Patricia Rogers for use in Methods Lab projects. It follows to some extent the BetterEvaluation Rainbow Framework.